Association Between Low Birth Weight and Stunting Incidence: Scoping Review - Silviatul Amalia; Ismarwati Ismarwati (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Babies with low birth weight have slower growth and development compared to babies with normal birth weight as they experience digestive disorders resulting in poor nutritional intake. If this condition lasts longer without inadequate nutrition, children can be infected and experience stunting. This research aims to examine the association's evidentiary basis between low birth weight and stunting. Inclusion criteria: Indonesian or English articles published in the last 5 years; original articles focused on low birth weight on stunting incidence.  This study used PRISMA-ScR Checklist with 5 stages referring to Arksey and O'Malley. The article search used 4 databases: PubMed, DOAJ, Wiley Online Library, and EBSCO. The result is a total of 16 out of 2704 articles obtained were relevant and met the inclusion criteria. This review generated two themes: the factors and impact of low birth weight.  It can be concluded that babies with low birth weight significantly correlate with stunting incidence.